Clarifying the Purported Association between Isotretinoin and Inflammatory Bowel Disease - Coughlin, Steven S. (J Environ Health Sci, 2015)
Isotretinoin was approved by the Food and Drug Administration (FDA) in 1982 and revolutionized acne therapy. Soon afterwards, case reports appeared suggesting a link between inflammatory bowel disease and use of isotretinoin. As reviewed in this article, an increasing number of case-control and prospective (cohort) studies have been reported that examined associations between use of isotretinoin and inflammatory bowel disease. Published epidemiologic studies of the use of isotretinoin and risk of Crohn's disease and ulcerative colitis vary according to whether the design was a case-control study or cohort study and by other important design differences. The strengths and limitations of the studies, such as their ability to control for important confounding variables (e.g., the severity of acne and use of antibiotics), also differ widely. Results across epidemiologic studies have been inconsistent and most studies have not found a strong association or a dose-response relationship. Based upon results from laboratory studies, several biological mechanisms have been proposed to account for either a positive (pathogenic) or inverse (protective) association between isotretinoin and inflammatory bowel disease. Although epidemiologic study findings are generally consistent with a correct temporal relationship (i.e., exposure to isotretinoin preceded the onset of inflammatory bowel disease), Crohn's disease and ulcerative colitis often have an insidious onset with some symptoms occurring well before a clinical diagnosis of inflammatory bowel disease is made. Taken overall, results from epidemiologic (case-control and cohort) studies completed to date do not show a consistent association between isotretinoin use and risk of inflammatory bowel disease. There is no clear evidence of a causal link.